LOCOREGIONAL FLAPS IN ONCOPLASTIC SURGERY AND BREAST RECONSTRUCTION - Figueiredo, Carolina Lamac; Andrade, Raffaela Levy; Urban, Cícero de Andrade (Mastology, 2017)
Introduction: Conserving surgery in the treatment of breast cancer, in association with radiotherapy, has replaced mastectomy in most cases. However, depending on the location and size of tumor, the classic conservative surgery can present unfavourable aesthetic results and high levels of commitment of the surgical margins. The oncoplastic breast surgery can have high local control rates and cause minimum breast deformities, leading to a better aesthetic result. Objective: To report cases of 30 patients with primary unilateral breast carcinoma who underwent oncoplastic surgery between 2013 and 2015. Methods: We used local and regional dermo-glandular rotation techniques. The average age of patients was 58.9 years. The average tumor size was 2.53 cm. Three patients had close or positive surgical margins and underwent a new surgical procedure. Results: The aesthetic result was evaluated by the BCCT.core program and was considered excellent in 11 cases, good in 12 cases and regular in 7 cases. Six patients had postoperative complications. Conclusion: The use of local and regional dermo-glandular rotation techniques allows extensive resections in breast conserving surgery, leading to a satisfying symmetry and a good aesthetic result without the need of symmetrization, with low postoperative complication rates and high rates of free surgical margins